Effect of trace elements and nutrients on diabetes and its complications: a Mendelian randomization study - Jia, Ming-Jie; Chen, Long (Frontiers in Nutrition, 2024)
Background: Multiple clinical studies have observed a close relationship between serum trace elements and nutrients and diabetes and its complications, but it remains unclear whether there is a genetic causal effect between serum trace elements and nutrients and diabetes and its complications. Objective: This study aims to investigate the causal effects of serum trace elements and nutrients on diabetes and its complications using Mendelian randomization methods. Methods: The single nucleotide polymorphisms of serum trace elements and vitamins, as exposure factors, were sourced from the published UK Biobank database and public databases of genome-wide association studies. The genome-wide association study data of diabetes and its complications, as outcome events, were sourced from the FinnGen Biobank database. Mendelian randomization methods were employed to explore the causal relationships between 9 trace elements and 6 nutrients and diabetes and its complications. The causal relationships were inferred using inverse variance weighting, MR Egger, weighted median, simple model, and weighted model methods. Sensitivity analyses, including heterogeneity tests, horizontal pleiotropy tests, MR-PRESSO tests, and leave-one-out analysis, were conducted to evaluate the robustness of the study results. Results: Mendelian randomization analysis revealed that selenium was linked to an elevated risk of T2D.Vitamin B6 was correlated with an increased risk of neurological complications in type 2 diabetes.Magnesium exhibited a negative causal relationship with the risk of T1D.Carotene was linked to a higher risk of renal complications in T1D.Vitamin B12 showed a negative causal relationship with renal complications in T1D.Carotene was connected to a higher risk of neurological complications in T1D.Potassium and vitamin B6 exhibited negative causal relationships with neurological complications in T1D.Vitamin E showed a negative causal relationship with peripheral circulation complications in T2D. Conclusion: The findings from univariable and multivariable Mendelian randomization studies substantiate the causal relationships between trace elements and nutrients and different subtypes of diabetes and their complications.These findings hold significant clinical implications for developing targeted prevention and treatment strategies for diabetes and its complications.